2009
DOI: 10.1055/s-0029-1216362
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Hemicraniectomy for Space-occupying Cerebral Infarction

Abstract: The development of a space-occupying hemispheric infarction occurs in a subset of patients with ischaemic cerebrovascular stroke. It is a life-threatening condition with a high mortality rate of up to 80% with medical therapy alone. Previous retrospective and uncontrolled case series have suggested that decompressive hemicraniectomy can significantly reduce mortality to 20-30% compared to conservative treatment. This evidence has now been confirmed by the data of prospective randomised studies. The data also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
1
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(132 citation statements)
references
References 75 publications
8
111
1
12
Order By: Relevance
“…5,16 Involvement of the dominant cerebral hemisphere should not preclude surgical decompression because long-term differences in clinical outcome after DH are not significantly different from those seen in patients with nondominant-hemisphere infarctions. 9,27,29 Intravenous tPA administration was not a significant predictor of poor outcome after DH. Several other studies have failed to find a significant effect of tPA administration on poor outcome and mortality after surgery as well.…”
Section: Discussionmentioning
confidence: 85%
“…5,16 Involvement of the dominant cerebral hemisphere should not preclude surgical decompression because long-term differences in clinical outcome after DH are not significantly different from those seen in patients with nondominant-hemisphere infarctions. 9,27,29 Intravenous tPA administration was not a significant predictor of poor outcome after DH. Several other studies have failed to find a significant effect of tPA administration on poor outcome and mortality after surgery as well.…”
Section: Discussionmentioning
confidence: 85%
“…Historically, there has been reluctance to perform this operation because of a high rate of mortality and profound morbidity in survivors. Until recently, only case series and nonrandomized case-control studies suggested any benefit of decompressive craniectomy [39][40][41][42][43]. Several recent randomized controlled trials have demonstrated improved survival after decompressive craniectomy in certain stroke populations [6,[44][45][46].…”
Section: Osmotherapymentioning
confidence: 99%
“…(Mori et al, 2004) On the other hand, there are other studies which do not confirm the effect of timely " preventive " operations and these studies encourage clinicians to be more conservative and to wait for the time of developing the mass effect and midline shift. (Uhl et al, 2004;Rabinstein et al, 2006) Bar et al demonstrated in his studies that the size of ischemia does not have any influence on the favourable outcome (mRankine 0-4) assessed 3 months after the operation. He also did not identify the timing as an important variable affecting the outcome but in his work only a few patients were indicated early and this masked the benefit of early versus late surgery.…”
Section: Indicationsmentioning
confidence: 99%